1998
DOI: 10.1046/j.1464-410x.1998.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

How to select patients suitable for transurethral microwave thermotherapy: a systematic evaluation of potentially predictive variables

Abstract: Objective  To identify clinical variables useful in predicting outcome after transurethral microwave thermotherapy (TUMT) of the prostate with Prostasoft v. 2.0. Patients and methods  Thirty‐eight men with symptomatic benign prostatic hyperplasia (BPH) were treated with TUMT using the Prostatron device with the low‐energy (v. 2.0) software. Before and 6 months after treatment symptoms were evaluated using the Madsen‐Iversen (M‐I) symptom score, a clinical examination and suprapubic pressure‐flow measurement, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…Damage to sensory nerves and reinnervation could explain the limited duration of symptomatic improvement seen in this study and could explain why we found no changes of Qmax or on ultrasonography, and only retrograde ejaculation in one of 13 patients. The conclusion of an extensive analysis of urodynamic parameters was that there was no useful predictive potential in the common urodynamical parameters including the Schäfer grading of obstruction used by us (9). This we have confirmed.…”
Section: Discussionsupporting
confidence: 58%
“…Damage to sensory nerves and reinnervation could explain the limited duration of symptomatic improvement seen in this study and could explain why we found no changes of Qmax or on ultrasonography, and only retrograde ejaculation in one of 13 patients. The conclusion of an extensive analysis of urodynamic parameters was that there was no useful predictive potential in the common urodynamical parameters including the Schäfer grading of obstruction used by us (9). This we have confirmed.…”
Section: Discussionsupporting
confidence: 58%
“…The impact of traditionally used subjective and objective parameters on treatment outcome has been studied [10][11][12] , but the results are not reliable. In this study, all parameters after TURP changed significantly, from 55.1 to 116%, and that determined the overall effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tubaro et al [1995] evaluated the e¡ect of TUMTand strati¢ed patients according to the type of obstruction (constrictive and compressive). In studies selecting patients for TURP, one-dimensional classi¢cations of obstruction based on the Abrams^Gri⁄ths nomogram [Abrams, 1994] or the SchÌfer nomogram [SchÌfer, 1995] are usually applied [Jensen et al, 1996;Walde¤ n et al, 1998;Rodrigues et al, 2001]. In the present study, classi¢cation according to the SchÌfer nomogram and DAMPF scale was used to grade BOO in simple terms of more or less obstructed.…”
Section: Discussionmentioning
confidence: 99%
“…TURP is associated with signi¢cant morbidity, mortality, and retreatment rates even when performed by experienced urologists. Approximately 25^40% of patients claim dissatisfaction with the outcome of surgery and the results have been reported to be less favorable in patients with lower grades of obstruction [Jensen et al, 1996;Walde¤ n et al, 1998;Rodrigues et al, 2001]. The early identi¢cation of these patients, who are not expected to bene¢t from operation, becomes an important issue.…”
Section: Introductionmentioning
confidence: 99%